Characteristics of dissolved organic matter in lakes with different eutrophic levels in southeastern Hubei Province, China - Ren, Weixiang; Wu, Xiaodong; Ge, Xuguang; Lin, Guiying; Zhou, Mengdie; Long, Zijie; Yu, Xinhui; Tian, Wei (Journal of oceanology and limnology, 2021)
Dissolved organic matter (DOM) plays a crucial role in both the carbon cycle and geochemical cycles of other nutrient elements, which is of importance to the management and protection of the aquatic environments. To achieve a more comprehensive understanding the characteristics of DOM in the Changjiang (Yangtze) River basin, water samples from four natural lakes (Xiandao, Baoan, Daye, and Qingshan) in southeastern Hubei Province in China with different eutrophication levels were collected and analyzed. The optical characteristics were analyzed using ultraviolet-visible spectrophotometry and excitation-emission matrix spectroscopy coupled with parallel factor analysis. The results show that: (1) two humic-like components (C1 and C2) and two protein-like substances (C3 and C4) of DOM were identified in all waterbodies; (2) C3 originated primarily from the degradation of microalgae and contributed substantially to humic-like components during transformation. C4 was widely present in the Changjiang River basin and its formation was related to microbial activity, rather than algal blooms or seasons. Influenced by the water mixing, the protein-like components were more likely to be transformed by microorganism, whereas humic-like components were more easily to be photobleached; (3) the concentration of DOM and the fluorescence intensity of humic-like components gradually increased with rising lake eutrophication levels. With respect to protein-like components, only C3 showed changes along the eutrophication gradients; (4) DOM showed a high affinity with permanganate index (COD Mn ) and chlorophyll a (chl a ) while the relationship was variable with phosphorus. This study helps us systematically understand the DOM characteristics, microbial activities, and pollutant transformation in the Changjiang River basin and provides reference to the ecological restoration of aquatic environments.